Conservative treatment: influence on clinical parameters of subjects on hemodialysis - Tavares da Silva, Sandra; Lanes Ribeiro, Rita de Cássia; de Oliveira Barbosa Rosa, Carla; Minardi Mitre Cotta, Rosângela (O Mundo da Saúde, 2013)
diagnosis of Chronic Kidney Disease (CKD) leads to the implementation of measures that are delaying undergoing hemodialysis (HD) and improve clinical parameters. The aim of this study was to analyze the epidemiological and clinical characteristics of individuals with CKD who underwent HD or not conservative treatment (CT). Data were collected from medical records of 65 participants who were interviewed about the diagnosis and treatment of CKD. For data analysis, subjects were divided between those who underwent CT or not and as to the time of CT less than, equal to or greater than six months. Hypertension and diabetes mellitus were the main causes of CRD, which were diagnosed, in most cases, by a nephrologist. Most individuals which did not receive a conservative treatment were diagnosed as having CRD in a hospital settting. Individuals who underwent CT showed better biochemical parameters, especially those who did so for more than six months. The TC mainly conducted by multidisciplinary teams, can contribute to improving the outcomes of CKD in both pre-dialysis and during HD treatment.